Management and Thinking on the Treatment of Cancer Patients During the COVID-19 - Pan, Shuangyue; Jiang, Jiahong; Chen, Zheling; Yang, Liu (Frontiers in Molecular Biosciences, 2021)
Coronavirus disease-2019(COVID-19) has spread rapidly around the world and has become a public health emergency of international concern. The weekly epidemiological report issued by the WHO pointed out that new coronavirus variants have appeared in 131 countries and regions which presents the current epidemic situation is still severe. As of now, the SARS-CoV-2 virus has been widespread worldwide for more than one year and poses a serious threat to the health of vulnerable groups such as malignancy, the elderly and immunocompromised. Compared with the general population, cancer patients with COVID-19 infection are more likely to have serious clinical adverse events, leading to higher mortality. There is no doubt that during the COVID-19 epidemic, no matter how to prevent infection or how to continue anti-tumor treatment, cancer patients are in a difficult situation. Meanwhile, an international patient with malignant Hodgkin’s lymphoma who was cured after being infected with the new coronavirus surprised us, and it inspires more scientists to explore the relationship between infection, immunity and tumors. Relevantly, through multi-disciplinary discussion, scientists put forward more new perspectives on the treatment of future tumors and the management of SARS-CoV-2 diseases. In this review, the impact of COVID-19 on cancer patients is discussed in detail and the recommendations for the diagnosis, treatment and management of cancer patients will be put forward under the challenge of COVID-19 epidemic. Furthermore, the safety and effectiveness of the SARS-CoV-2 vaccine will be discussed and we will also put forward our insights on cancer immunity.